Flyschoid deposits of Goriška Brda (Collio) between Soča (Isonzo) River and Idrija (Iudrio) River - facies and paleoenvironments - Tunis, Giorgio; Radrizzani Pirini, Camilla (Geologija, 1987)
Presented is the interpretation of environments of main facies associations types in Goriška Brda. The high diversity of studied depositional facies bears evidence of profound differences of environments during deposition of flyschoid beds. Environments from relatively deep sea to those of the external margin of the platform, and those of delta (delta front and delta plain) can be established.